ChemInform Abstract: Enantioselectively‐Catalyzed Reactions with (E)‐2‐Alkenoyl‐pyridines, Their N‐Oxides, and the Corresponding Chalcones. Issue 33 (19th August 2014) - Desimoni, Giovanni; Faita, Giuseppe; Quadrelli, Paolo
Abstract Review: 89 refs.